Kebijakan dan Implementasi Analisis Jabatan dalam Mendukung Pengembangan SDM Aparatur - Kurniawan, Iwan; Taufik, Taufik (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
(Policy and Implementation of Position Analysis in Support of Apparatus HR Development) This study aims to determine and analyze the policy and implementation of job analysis in the development of human resources of civil servants. Job analysis in the government sector is an important part of integral HR Planning in ensuring the suitability between organizational needs and the availability of manpower. This study uses a descriptive qualitative method. Descriptive qualitative methods in processing data in the form of data reduction, data presentation, and drawing conclusions and verification. The research data is in the form of secondary data from regulations, references, and scientific journals. Data collection techniques used include observation and analysis of related documents. This study concludes that the policy and roadmap for the development of human resources of civil servants have been supported in the regulatory and strategic planning and operational systems based on job analysis which produces job specifications and job descriptions that are broken down into job competency standards in an ongoing effort to place competent human resources of civil servants. Professional human resource performance and quality and effective governance are the initial capital for empowering an organization. The enthusiasm of the leadership and all civil servants to work together to empower human resources and the organization. Acceleration to realize the ideals of bureaucratic reform by all levels of the bureaucracy. in building a clean, accountable, transparent and authoritative government through e-government based on HR competencies in order to make changes in improving HR management of government apparatus. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis kebijakan dan implementasi analisis jabatan dalam pengembangan SDM aparatur. Analisis jabatan di sektor pemerintahan merupakan bagian penting dari Perencanaan SDM secara integral dalam memastikan kesesuaian antara kebutuhan organisasi dengan ketersediaan tenaga kerja. Penelitian ini menggunakan metode kualitatif deskriptif. Metode kualitatif deskriptif dalam mengolah data berupa reduksi data, penyajian data, dan menarik kesimpulan dan verifikasi. Data penelitian berupa data sekunder dari regulasi, referensi, dan jurnal ilmiah. Teknik pengumpulan data yang digunakan meliputi observasi dan analisis dokumen terkait. Penelitian ini menyimpulkan bahwa kebijakan dan roadmap pengembangan SDM aparatur telah didukung pada tatanan regulasi dan perencanaan strategis serta operasional berbasis analisa jabatan yang menghasilkan deskripsi pekerjaan dan spesifikasi pekerjaan dalam upaya berkelanjutan menempatkam SDM aparatur yang berkompeten. Kinerja dan kualitas SDM yang profesional serta ketatalaksanaan yang efektif merupakan modal awal dari pemberdayaan suatu organisasi. Semangat pimpinan dan seluruh aparatur untuk secara bersama-sama saling bahu membahu untuk pemberdayaan SDM dan organisasi. Akselerasi mewujudkan cita-cita reformasi birokrasi oleh seluruh jajaran birokrasi. dalam membangun pemerintahan yang bersih, akuntabel, transparan dan berwibawa melalui e-government berbasis kompetensi SDM guna melakukan perubahan dalam memperbaiki manajemen SDM aparatur pemerintah.